Structural Intensity Characterization of Composite Laminates Subjected to Impact Load - 王东方 贺鹏飞 刘子顺 (Shanghai jiao tong da xue xue bao, 2008)
Structural intensity （SI） characterization of composite laminates subjected to impact load was discussed. The SI pattern of the laminates which have different fiber orientations and boundary conditions was analyzed. The resultant forces and velocities of the laminates were calculated, and the structural intensity was evaluated. The SI streamlines of carbon fiber reinforced epoxy composite laminates and the steel plates were discussed. The results show that the SI streamlines of the graphite/epoxy laminates are different from that of the steel plates, and the SI streamlines are influenced by the boundaries, the stacking sequence of the composite laminates. The change of the historical central displacement of the graphite/epoxy laminates is fasten than that of the steel plates.